From the Earth to the Sun: the quest for the Astronomical Unit by means of the 1761 and 1769 Venus transits. - Lovisetti, Luisa (Alma Mater Studiorum - Università di Bologna, 2021)
In the mid-eighteenth century, the primary and most urgent astronomical problem was to determine the exact value of the Earth-Sun distance (the so-called Astronomical Unit, A.U.). With that value in hand, thanks to Kepler’s third law, all the planet distances would have been easily derived and, as a consequence the entire solar system real dimension would have been determined too. The most promising methods for measuring the A.U., due to Halley and Delisle, were taking advantage of a rare phaenomenon: Venus transit over the Sun. It would have been sufficient that two observers, located in the two Earth hemispheres, had taken accurate measures of the transit to derive from the solar parallax and hence the A.U. The phaenomenon is rare but occurs always in close pairs and thus the attention of the whole scientific community was engaged twice in the eighteenth century: in 1761 and in 1769. While the European powers were fighting in the Seven Years War and in the subsequent struggles for colonial hegemony, 250 astronomers and scholars from different nations, animated by a common purpose in the spirit of Enlightenment, gave life to a joint venture, never attempted before, leaving for the farthest and most inaccessible locations of the known world, such as Siberia, the island of Newfoundland and the mysterious Australia, to observe Venus transit. Along with the astronomical results, those expeditions also improved geographical knowledges, discovered new lands, gave an impulse to the production of scientific instruments, resulted in collection of natural samples and, above all, constituted the first international and collaborative project in the whole history of science. At the crucial point, some astronomers faced a desolately cloudy sky, one passed out from his emotions, others had not even reached their destination, and someone never returned home. This is their story.